Detection of diffusion welding defects by thermal ndt of rectifier elements; The Soviet journal of nondestructive testing; Vol. 19, iss. 5 - Bragina L. A.; Vavilov V. P. Vladimir Platonovich; Ivanov A. I.; Korol'kov O. M.; Surzhenkov G. N.; Khutoryanskii E. D. (1983, 1983)
Problems of flaw detection in contact joints in rectifier elements (RE) of semiconductor devices are considered investigating the possibility of applying thermal nondestructive testing to such elements.